Экспериментальное определение донного рельефа на базе исследований нижнего участка р. Самара - Дубовик, Денис Дмитриевич; Борохович, Юлия Игоревна (НТУ "ХПИ", 2017)
Экспериментальное определение донного рельефа осуществляется путем измерения глубин исследуемой части ИВ, лабораторного определения мутности воды и скорости осаждения содержащихся в воде веществ. Далее выполняется приближенная оценка объема осаждающегося ила для исследуемого участка искусственного водохранилища на основе последовательно выполненных двух измерений глубин через определенный интервал времени. Одновременно с измерением глубин с заданным распределением точек измерения выполняется забор воды для лабораторного определения ее мутности и скорости осаждения ила.

Experimentally determine the bottom relief on the basis of studies of the lower section of the river. Samara. To build a route for measuring depths and digitizing depths, we used the built-in Android application, Androzik. Along with measurements of depths, water turbidity and sedimentation rate were determined. About 2,000 depth points were obtained, the data was transferred to the GIS platform, resulting in a bottom relief model, the area and volume of the reservoir. Laboratory tests of water samples were conducted on a number of parameters, the most important of which is the "turbidity" for modeling the sludge formation process. In the course of expedition studies of the cross-section profiles of the reservoir-prototype, the information was obtained in the form of direct measurements of the depths in the cross-sections of the given cross sections. Digitization and processing of cartographic data (topographic maps, remote sensing images) are carried out in the appropriate sections of the dissertation research using special techniques. Measurements were made using echolot and GPS devices. For an approximate calculation of the volume of the low, experimental data on the distribution of the turbidity of water and the rate of sedimentation of suspended solids are used. According to the approximate method of estimating the amount of the nitrate deposited during the year in the specified zones of the reservoir - the prototype. The bottom relief was determined experimentally on the basis of studies of the lower section of the river. Samara.
Experimental determination of the denon relief on the basis of the research of the lower site of r. Samara
Keywords: искусственное водохранилище; водозабор; объем наилка; картографические данные; bottom relief; artificial reservoir; water intake